The Role of Profitability in Corporate Sustainable Growth: An Empirical Analysis of Indonesian Listed Companies - Elia Rossa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the dynamic and competitive business environment, profitability has been recognized as a fundamental determinant of corporate sustainable growth. However, the complex relationship between profitability and sustainable growth, particularly through the mediating role of firm performance, remains understudied in emerging markets like Indonesia. This study examines the impact of profitability on corporate sustainable growth and investigates the mediating role of firm performance in this relationship among companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach with Structural Equation Modelling (SEM), this research analyses panel data from 112 companies listed on the IDX during 2018-2023, resulting in 672 observations. Profitability was measured using Return on Assets (ROA), sustainable growth using Sustainable Growth Rate (SGR), and firm performance using Tobin's Q. Data were analyzed using PLS-SEM to test both direct and mediating relationships. The findings reveal that profitability has a strong positive and significant impact on sustainable growth (β = 0.417, t = 9.328, p < 0.001), representing the highest path coefficient among all financial determinants examined. Firm performance significantly mediates the relationship between profitability and sustainable growth (indirect effect = 0.096, p < 0.001), indicating partial mediation. The model explains 47.9% of the variance in sustainable growth (R² = 0.479). Profitability emerges as the most critical financial determinant of sustainable growth in Indonesian listed companies. The study confirms that profitability influences sustainable growth both directly and indirectly through enhanced firm performance, providing dual pathways for growth enhancement. These findings have significant implications for corporate financial management and investment decision-making.